Compressive behavior of axially loaded circular hollow concrete columns reinforced with GFRP bars and spirals. (10th January 2019) - AlAjarmeh, O.S.; Manalo, A.C.; Benmokrane, B.; Karunasena, W.; Mendis, P.; Nguyen, K.T.Q.
Highlights: GFRP-reinforced hollow and solid concrete columns under concentric load. Effect of inner-to-outer ( i/o ) diameter ratio on hollow concrete columns. Axial design load prediction for GFRP-reinforced hollow concrete columns. Failure stress index for GFRP-reinforced hollow concrete columns. Abstract: This study explored the use glass-fiber-reinforced-polymer (GFRP) bars and spirals as reinforcing materials in hollow concrete columns in order to mitigate steel-related corrosion problems and understand the fundamental behavior of such construction system under the applied loads. Four concrete columns 250 mm in external diameter and reinforced longitudinally with six 15.9 mm diameter GFRP bars were cast with different inner diameters (0, 40, 65, and 90 mm) and tested under concentric axial loading. Based on the experimental results, increasing the inner-to-outer diameter ratio up to 0.36 in hollow GFRP reinforced columns changed the failure behavior from brittle to pseudo-ductile. Moreover, the hollow GFRP reinforced columns exhibited higher deformation capacity and higher confinement efficiency compared to the GFRP-reinforced solid columns and steel-reinforced hollow columns. A theoretical model considering the confined-concrete compressive strength and axial strain of 0.0025 in longitudinal GFRP bars can accurately predict the axial-load capacity of hollow concrete columns.